GLOBAL SEXUAL DEVIANCY: LEARNING FROM AMERICA’S MISTAKES - Daniel, Velasco (European Scientific Journal, ESJ, 2014)
Sexual Deviancy is a global issue, and efforts to standardize treatment have produced programs that do not support cultural understanding and sensitivity. With the rise of sexual offenses around the world, and the demand for public safety, sex offender treatment programs must be examined before countries without treatment and management programs adopt the ones currently being implemented. In order to gain a better understanding on a global scale, the perceived effectiveness of sex offender treatment programs in the United States and Japan was evaluated by administering a questionnaire to a sample of the general population and by interviewing mental health professionals in order to discover if treatment modalities exist that would provide cross-cultural utility. The results suggest a need for further research on and implementation of sex offender treatment approaches that would be more effective than current programs. Results also revealed continued beliefs in sex offender myths, and a perceived ineffectiveness of current sex offender management laws.